2020
DOI: 10.1080/21655979.2020.1729322
|View full text |Cite
|
Sign up to set email alerts
|

MiR-211 protects cerebral ischemia/reperfusion injury by inhibiting cell apoptosis

Abstract: MicroRNAs (miRNAs) have emerged as critical regulators of neuronal survival during cerebral ischemia/reperfusion injury. Accumulating evidence has shown that miR-211 plays a crucial role in regulating apoptosis and survival in various cell types. However, whether miR-211 is involved in regulating neuronal survival during cerebral ischemia/reperfusion injury remains unknown. In this study, we aimed to explore the biological role of miR-211 in regulating neuronal injury induced by oxygen-glucose deprivation/reox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…Reportedly, lncRNAs can exert its biological functions via multiple mechanism, including functioning as a competitive endogenous RNA to modulate the downstream miRNAs [31,32]. In recent years, reportedly, miRNAs are pivotal regulators in the pathogenesis of neurodegenerative diseases [33][34][35]. In this work, miR-124-3p expression was decreased in a timeand dose-dependent manner in cells treated with MPP+.…”
Section: Discussionmentioning
confidence: 62%
“…Reportedly, lncRNAs can exert its biological functions via multiple mechanism, including functioning as a competitive endogenous RNA to modulate the downstream miRNAs [31,32]. In recent years, reportedly, miRNAs are pivotal regulators in the pathogenesis of neurodegenerative diseases [33][34][35]. In this work, miR-124-3p expression was decreased in a timeand dose-dependent manner in cells treated with MPP+.…”
Section: Discussionmentioning
confidence: 62%
“…24 Of note, inhibiting miR-27a-3p expression following Rgs1 silencing reverted the protective properties of Rgs1 silencing, further indicating that Rgs1 is a direct target of miR-27a-3p. A single miRNA may target multiple mRNAs and one mRNA may be targeted by multiple miRNAs, 12 our data imply that the anti-inflammatory as well as anti-apoptotic properties of miR-27a-3p are at least in part mediated through targeting Rgs1. Our data show for the first time that downregulation Rgs1 prevents inflammation and apoptosis in a model of cerebral I/R injury in vitro, and that this effect is directly modulated by miR-27a-3p.…”
Section: Dovepressmentioning
confidence: 62%
“…MiRNA is capable of inhibiting protein expression by specifically binding one or more 3 ʹ-UTR mRNA sequences, thereby regulating gene expression posttranscriptionally. 11,12 MiRNAs influence the pathogenesis of various diseases, including nervous system disorders, and are, therefore, considered potential therapeutic targets in the nervous system. 13 Cerebral ischemia/reperfusion injury alters the expression profile of many miRNAs that may be involved in the injury or recovery processes.…”
Section: Introductionmentioning
confidence: 99%
“…CIR injury, one of the major causes of death from stoke in the world, not only causes tremendous damage to human health, but also brings heavy economic burden to family and society [31,32]. CIR injury is a complex pathological process, and a study found that neuronal injury in the brain is an important cause of reperfusion injury [33,34]. Therefore, how to protect brain neuronal cells from CIR injury is an important research.…”
Section: Discussionmentioning
confidence: 99%